The Circulating Protease Persephone Is an Immune Sensor for Microbial Proteolytic Activities Upstream of the Drosophila Toll Pathway - Issa, Najwa (Mol Cell, 2018)
Microbial or endogenous molecular patterns as well as pathogen functional features can activate innate immune systems. Whereas detection of infection by pattern recognition receptors has been investigated in details, sensing of virulence factors activities remains less characterized. In Drosophila, genetic evidences indicate that the serine protease Persephone belongs to a danger pathway activated by abnormal proteolytic activities to induce Toll signaling. However, neither the activation mechanism of this pathway nor its specificity has been determined. Here, we identify a unique region in the pro-domain of Persephone that functions as bait for exogenous proteases independently of their origin, type, or specificity. Cleavage in this bait region constitutes the first step of a sequential activation and licenses the subsequent maturation of Persephone to the endogenous cysteine cathepsin 26-29-p. Our results establish Persephone itself as an immune receptor able to sense a broad range of microbes through virulence factor activities rather than molecular patterns.